Psychological impact of noise exposure among machine operators and non-machine operators in construction sites in Perak, Malaysia - Kee, Heng Yik (2019)
Noise from the construction activities is one of the severe issue of noise pollution where there must be noise pollution produced at every construction projects. In Malaysia, previous statistical report has stated that the construction sites have high exposure of several hazards especially the noise hazard where noise hazard was ranked 2 with frequency 134 out of 140 sites. The previous reports reveal that the noise hazard is one of the main causes of the occurrence of accidents in construction industry as noise hazard affect the safety and health among the construction workers. As the noise hazard is reported as serious issue among the construction industry in Malaysia, an impact of noise exposure need to be conducted in this study. This study is mainly focus in identifying the personal noise exposure level and the prevalence of psychological health effect symptoms among the machine operators and non-machine operators on construction site in Perak. Sixty-one construction workers were selected as respondents and categorized into machine operators group and non-machine operators group. All respondents were monitored for 8 hours working time using personal noise dosimeter for the personal noise monitoring. For the prevalence of psychological health effect symptoms due to noise exposure, questionnaires and interview sessions were done among the selected construction workers. The result obtained reveals that the personal noise exposure level among the construction workers is high where the mean of personal noise exposure level for machine operators group (81.81dBA) is significantly higher compared to the mean of personal noise exposure level for non-machine operators group (74.71dBA). Besides, the prevalence of psychological health effect symptoms is high among the construction workers where 93.5% of machine operators and 43.3% of non-machine operators feel tension when working in noisy work environment. Through the independent chi-square test, results with the p-value less than 0.05 show that there was significant differences between the machine operators and non-machine operators for several prevalence of psychological health effect symptoms where machine operators has significantly higher prevalence compare to non-machine operators. Lastly, result obtained through Binary Logistic Regression, it reveals that there is significant and positive coefficient between the personal noise exposure level and the prevalence of several psychological health effect symptoms on ear pain (p-value=0.011), noticeable change in hearing (p-value=0.007), and dizziness (p-value=0.016) for machine operators and sudden hearing loss (p-value=0.047), anger and aggressiveness (p-value=0.027), dizziness (p-value=0.050), stressful (p-value=0.031) and tension (p-value=0.028) in noisy work environment for non-machine operators in construction site.